Developing English by Specific Purposes (ESP) Materials Based on Needs Analysis for Banking Students to Success in the 5.0 Society Era. - Nurliah Nurliah; Yuriatson Yuriatson; Kaharto Kaharto (SMA Negeri 1 Bangkinang Kota, 2026)
The concept of needs analysis has evolved over several decades. Today, the needs analysis process has become much more comprehensive. The goal is to gather information about learners and establish the desired learning environment and atmosphere for learning English for Specific Purposes (ESP). This research was conducted at Sharia Banking Students of Islamic DDI Ambo Dalle University in Polewali Mandar. There were 17 Sharia Banking students. The researcher identified 12 themes and all were consistently rated highly by various respondents as suitable learning materials. The findings of this research are expected to serve as a reference point for further research, particularly in the areas of syllabus/RPS development and the development of English teaching materials for Sharia Banking students. There are many significant factors that can serve as useful guides when creating ESP materials for speaking, listening, reading, and writing sub-skills. Most of students prioritize vocabulary development and speaking skills driven by their goals of working in a bank and effectively serving foreign clients